2018
DOI: 10.1186/s12875-018-0839-x
|View full text |Cite
|
Sign up to set email alerts
|

Designing a framework for primary health care research in Canada: a scoping literature review

Abstract: BackgroundDespite significant investments to improve primary health care (PHC) delivery in Canada, provincial health care systems remain fragmented and uncoordinated. Canada’s commitment to strengthening PHC should be driven by robust research and evaluation that reflects our health policy priorities and responds to the needs of the population. One challenge facing health services researchers is developing and sustaining meaningful research priorities and agendas in an overburdened, complex health care system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
(21 reference statements)
0
10
0
Order By: Relevance
“…However, based on the present findings, together with those from other projects such as the collaborative action for person‐centred coordinated care initiative, 45 the introduction of PCC into the healthcare systems needs to be carefully followed and evaluated to identify effective practices. A priority‐driven research agenda has been suggested and may be useful to the GPCC to support healthcare decision‐making while using resources effectively 46 …”
Section: Discussionmentioning
confidence: 99%
“…However, based on the present findings, together with those from other projects such as the collaborative action for person‐centred coordinated care initiative, 45 the introduction of PCC into the healthcare systems needs to be carefully followed and evaluated to identify effective practices. A priority‐driven research agenda has been suggested and may be useful to the GPCC to support healthcare decision‐making while using resources effectively 46 …”
Section: Discussionmentioning
confidence: 99%
“…Since scoping reviews can be an arduous, yet transparent method for mapping research areas, some recently used it as either a stand-alone or supplementary tool in agenda-setting in various fields in health research [6,7,8,9]. Montesanti et al used it as a sole tool in generating key research themes in primary health care in Canada to contribute to the efficient and equitable use of limited funding, and possibly reduced duplication [6]. Alternatively, Ajumobi et al used a scoping review in developing introductory materials to guide the consultative process in setting Nigeria’s national malaria operational research agenda [7].…”
Section: Introductionmentioning
confidence: 99%
“…All participants viewed research in primary care as critical as most patient care occurs in this setting. This is supported by the literature that primary care is about relationships among physicians, patients, families, and communities; it is the backbone of the health system, and primary care research is needed to inform policy that sustain healthcare delivery and the commitment to improving population health (9,37,(43)(44)(45). Our project ndings, supported by other studies, suggest that it was important to foster an overarching culture that values and supports primary care research through the establishment of strong funding policies by government and funding institutions (38,44,(46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, emerging issues such as planetary health and primary care provider wellness are also important topics of research. Therefore, the future agenda for primary care is sophisticated and needs an interdisciplinary scientist workforce equipped to address identi ed gaps at clinical and policy levels to improve outcomes for populations served (5)(6)(7)(8)(9)(10). To that end, university primary care academic departments must support the development of primary care clinician scientist workforce and research production (11)(12)(13).…”
mentioning
confidence: 99%